(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
It is known that many experiments have shown that the duration of the growth period of bread wheat varies depending on various environmental factors. In particular, the duration of growth and the start time of development stages are mainly determined depending on temperature, precipitation, geographical latitude, and day length. For this purpose, in the experiments, when assessing the duration of the growing season of bread wheat varieties and samples in the studied collection nurseries, the main attention was paid to the selection and evaluation of early-ripening varieties with a short germination-heading period. According to the analysis results, the average duration of the germination-heading period of bread wheat varieties and samples was 3 days earlier compared to the standard Zamin-1 variety (179 days). It was also observed that the coefficient of variance series is 1.30-4.20, and the minimum indicators are 178-182 days. According to the results of statistical analysis of bread wheat variety samples, the duration of the germination-heading period according to the Mode indicator of the program was the most observed - 177 days.